2018
DOI: 10.18203/2320-1770.ijrcog20182412
|View full text |Cite
|
Sign up to set email alerts
|

Study on semen analysis in the evaluation of male infertility in coastal Karnataka, India

Abstract: INTRODUCTIONInfertility is a condition with psychological, economic, medical implications to the couple resulting in decreasing the quality of life, with a strong emphasis on child bearing. According to WHO infertility is a disease of reproductive system defined by failure to achieve the clinical pregnancy after 12 months or more of regular unprotected intercourse. It can also be defined as failure of couple to conceive after 12 months of regular intercourse without the use of contraception in women <35years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Regarding macroscopic semen analysis, the majority of the patients in our study had normal semen volume, appearance, pH, viscosity, and liquefaction time. Our findings in this regard closely resembled the findings from various other studies conducted in the regions 9,10,12 . These studies concluded that the semen volume is one of the most important factors associated with infertility.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding macroscopic semen analysis, the majority of the patients in our study had normal semen volume, appearance, pH, viscosity, and liquefaction time. Our findings in this regard closely resembled the findings from various other studies conducted in the regions 9,10,12 . These studies concluded that the semen volume is one of the most important factors associated with infertility.…”
Section: Discussionsupporting
confidence: 91%
“…The factors affecting the semen parameters in the country were not considered in our study, the significance of this age range in fertility issues cannot be correlated with the semen parameters at the moment. Interestingly, there exists a lot of evidence supporting the association between male age and reduced fertility after the age of 60 in other countries 9,10 , but no such evidence existed for the age range 30 to 39. Amongst different occupational groups, private businesses 129(42.4%) had the highest number coming for semen analysis followed by civil servants 88(28.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation